LITERATURE REVIEW: PENGARUH PIJAT BAYI TERHADAP PERUBAHAN KADAR BILIRUBIN DIRECT DAN BILIRUBIN INDIRECT PADA BAYI DENGAN TERAPI SINAR - Ika Yuni Susanti; Citra Adityarini Safitri (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Infant massage is one of the tactile stimulation and has become a hereditary tradition and has been studied in research in the fields of neonatal science, neurology, psychology, and several other health sciences. The incidence of hyperbilirubinemia in general is a physiological problem that occurs in almost 80% of newborns with prematurity and up to 60% of aterm newborns and occurs in the first week of life. This study aims to determine the implementation of massage therapy in neonates to reduce bilirubin levels. The research method used literature review by searching articles obtained through databases including Science Direct, Elsevier and Google Scholar. The results showed five articles involving neonates in five countries with a randomized control trial (RCT) design, stating that infant massage therapy is the most influential in reducing the degree of neonatal jaundice in the group given massage therapy because it can stimulate defecation. In addition, the provision of physiological massage therapy can improve the circulation of blood flow, lymph and tissue fluids thereby increasing bilirubin output.